Przemiany w strukturze demograficznej ludności wiejskiej wyznacznikiem przekształceń w rozmiarach i kierunkach kształcenia rolniczego - Wołoszyn, Jan (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2002)
The development of agricultural education is determined by many factors, among others by the demographical processes being considered of great importance. They have initiated long before the political system transformation. In the seventies, decreasing tendency in the number of children and teenagers, especially within farm families, started to be observed in rural areas. The forecasts show that this group of population is going to decline significantly by the year 2030, even to 65.1% comparing with the present situation. Planning the future shape of the education system and the number of students attending agricultural schools we cannot ignore these facts. They indicate on necessity to reduce the number of students completing the typically agricultural majors and to give the youth the opportunity to learn professions connected with jobs offered in services, processing and trade.